2014
DOI: 10.1126/science.1252943
|View full text |Cite
|
Sign up to set email alerts
|

Human tRNA synthetase catalytic nulls with diverse functions

Abstract: Genetic efficiency in higher organisms depends on mechanisms to create multiple functions from single genes. To investigate this question for an enzyme family, we chose aminoacyl tRNA synthetases (AARSs). They are exceptional in their progressive and accretive proliferation of noncatalytic domains as the Tree of Life is ascended. Here we report discovery of a large number of natural catalytic nulls (CNs) for each human AARS. Splicing events retain noncatalytic domains while ablating the catalytic domain (CD) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 34 publications
5
110
1
Order By: Relevance
“…The variant is readily translated and imported into mitochondria, suggesting a noncanonical mitochondrial function. This phenomenon is reminiscent of other examples of synthetase fragments and supports the hypothesis that alternative splicing of mRNA transcripts of aaRS is a way to enlarge aaRS additional functions in higher eukaryotes (27,28). Altogether, our results significantly improve our understanding of hmtThrRS and provide a basis for further investigations of TARS2-related human diseases.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The variant is readily translated and imported into mitochondria, suggesting a noncanonical mitochondrial function. This phenomenon is reminiscent of other examples of synthetase fragments and supports the hypothesis that alternative splicing of mRNA transcripts of aaRS is a way to enlarge aaRS additional functions in higher eukaryotes (27,28). Altogether, our results significantly improve our understanding of hmtThrRS and provide a basis for further investigations of TARS2-related human diseases.…”
supporting
confidence: 61%
“…Existence of an Alternative Splicing Variant with Possible Non-translational Function-Recently, it was reported that nearly all aaRS genes in humans encode multiple splicing variants, creating a large number of aaRS-related catalytic nulls (28). These catalytic nulls usually keep their non-catalytic domains and exhibit deletions or truncations in the catalytic core, inducing loss of tRNA aminoacylation activity.…”
Section: Human Mitochondrial Thrrs Misactivates Ser and Mainly Uses Tmentioning
confidence: 99%
“…Some of these catalytically inactive splice variants fall into the SEP regime in terms of their small size. Interestingly, each of the AARS variants demonstrated novel regulatory activities spanning a variety of physiological processes, including cell differentiation and proliferation, transcriptional regulation, and inflammatory response, which are distinct from the original aminoacylation function (Lo et al, 2014). In addition to the fact that alternative splicing is able to produce functional SEPs, SEPs can also be generated via polycistronic translation of a given RNA transcript.…”
Section: Sep Characteristicsmentioning
confidence: 99%
“…Human TyrRS has been proposed to generate MiniTyrRS and EMAPII fragments by two different mechanisms: proteolytic cleavage 25 and alternative splicing 35 . To test the proteolytic hypothesis, we used transgenic flies expressing TyrRS-HA that cannot be alternatively spliced.…”
Section: Matrix Metalloproteinase Mmp2 Cleaves Tyrrs In Loser Cellsmentioning
confidence: 99%